Keberbaktian Remaja pada Ayah: Pendekatan Indigenous Psychology - Indah Pratiwi; Ivan Muhammad Agung (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2022)
This study aims to explore how and why teenagers devoted to their fathers, in terms of gender. The research method used an indigenous psychology approach with the number of research participants were 406 teenagers in the city of Pekanbaru. Participants were asked to answer the question